A Brønsted Acid Catalyzed Redox Arylation1. Issue 33 (3rd March 2014) - Peng, Bo; Huang, Xueliang; Xie, Lan‐Gui; Maulide, Nuno
Abstract A Brønsted acid catalyzed redox arylation of ynamides that employs aryl sulfoxides as the arylating agents is reported. This metal‐free transformation proceeds at room temperature and efficiently affords α‐arylated oxazolidinones in a redox‐neutral, atom‐economic fashion.